The Effect of Job Stress on Employee Proactive Behaviour: The Role of Job Remodeling - Zhengdong Li, Xuan Guo (Forest Chemicals Review)
Proactive behavior is an important topic in the field of organizational behavior in recent years. This study examines the effects of challenge-obstructive stress on employee proactive behavior, with emphasis on the mediating role of job remodeling and the moderating role of leader-member exchange. The results show that challenging stressors positively affect employee proactive behavior, while impeding stressors negatively affect employee proactive behavior. Job remodeling partially mediated the relationship between challenging stress and proactive behavior, and partially mediated the relationship between obstructive stress and proactive behavior. Leader-member exchange attenuates the negative effects of obstructive stress on job remodeling. The above research provides a new explanation for “how to improve employees” proactive behavior under increasing work pressure" and has important theoretical and practical significance.